Influence of radiation treatment technique (IMRT vs. 3D-RT) on acute toxicity and prognostic factors for survival for anal cancer - Sauter, Christina; Peeken, Jan C.; Borm, Kai; Diehl, Christian D.; Munch, Stefan; Combs, Stephanie E.; Dapper, Hendrik (Scientific Reports, 2022)
We compared our institutional experience with intensity-modulated radiotherapy (IMRT) and 3D-conformal radiotherapy (3D-RT) for definitive treatment of primary anal cancer. We performed a single-institution retrospective review of all patients with anal squamous cell carcinoma treated with definitive (chemo) radiotherapy with curative intent from 2004 through 2018. We assessed several prognostic factors in respect to relevant survival endpoints. In addition, acute toxicities were determined and compared between IMRT and 3D-RT patients. This study included 94 patients (58 IMRT, 36 3D-RT). Mean follow up for all patients, for IMRT and 3D-RT patients was 61 months (range 6–176), 46 months (range 6–118), and 85 months (range 6–176), respectively. 5-year overall survival (OS) was 86%, disease-free survival (DFS) was 72%, and colostomy-free survival (CFS) was 75% in the IMRT cohort. In the 3D-RT cohort, OS was 87%, DFS was 71%, and CFS was 81% (all p > 0.05). Male gender and Karnofsky Index (KI) were revealed as independent prognostic factors for 5-year OS (p = 0.017; p = 0.023). UICC stage was an independent prognostic factor for DFS and CFS (p = 0.023; p = 0.042). In addition, the pre-treatment leukocyte count was an independent prognostic factor for CFS (p = 0.042). Acute grade ≥ 3 toxicity was not significantly different between IMRT and 3D-RT patients, but the IMRT cohort had favorable outcomes. This study confirmed IMRT as the primary definitive treatment of anal cancer. With similar survival rates, IMRT had the potential to reduce acute toxicity by sparing organs at risk. Promising prognostic factors such as BMI, KI, and leucocyte and hemoglobin levels should be further investigated.
CRIS-Team Scopus Importer:2023-03-08